Lions at lunchtime - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 1998)
The magic tree house takes Jack and Annie to Africa where they meet up with wonderful wild animals, a very hungry warrior, and where they even solve a riddle.
"A stepping stone book."
"RL:2.0"--cover p. [4].
Keywords: Tree houses -- Fiction; Magic -- Fiction; Animals -- Africa -- Fiction; Africa -- Fiction